Analisis Pengaruh Gaya Hidup, Literasi Keuangan dan Inklusi Keuangan terhadap Perilaku Keuangan Generasi Z di Jawa Barat - Firly Amelya Hidayat; V. Santi Paramita (IPM2KPE, 2024)
This research aims to identify the influence of lifestyle, financial literacy and financial inclusion on the financial behavior of generation Z. This research method uses quantitative methods with a descriptive and associative approach with data analysis techniques using multiple regression. The population in this study is Generation Z residents who live in West Java, amounting to 11,886,058 million. The sample was determined using a simple random sampling technique with a sample size of 100 from 16 cities. The results of this research show that partially and simultaneously, lifestyle, financial literacy and financial inclusion have a positive influence on the financial behavior of generation Z. The implications of the results of this research direct that the promotion of a healthy, frugal and planned lifestyle with the support of financial literacy and financial inclusion needs to be carried out intensively use various social media. Keywords: Lifestyle, Financial Inclusion, Financial Literacy, Financial Behavior